0690 The Association Of Meis1 Gene In Restless Leg Syndrome And Rls Related Phenotypes But Not With Chronic Insomnia Disorder. (27th April 2018) - El Gewely, M; Melanie, W; Lan, X; Sophie, Y; Rouleau, G; Montplaisir, J; Desautels, A; Warby, S
Abstract: Introduction: Chronic insomnia disorder (CID) and restless leg syndrome (RLS) are two common sleep disorders in the general population and are frequently comorbid. Two recent genome-wide assocaition studies (GWAS) have suggested that MEIS1 gene is a shared genetic basis between these two disorders, which is an intriguing finding that can change our understanding of the etiology of insomnia. While GWAS play a critical role in advancing our knowledge of sleep disorders, independent replication is a cardinal part of the GWAS methodology. Hence, the objective of our study is to evaluate the assoaiction between CID and MEIS1. Methods: We genotyped three MEIS1 variants in 705 CID patients with and without RLS to test for the suggested independent effect of MEIS1. Subjects were assigned to insomnia-only or insomnia+RLS groups by sleep medicine specialists. To confirm our genotyping results, we compared the allelic and genotypic distributions of our CID patients with ethnically matched controls and RLS cases. Polysomnography was used to quantify periodic leg movements in sleep, which supports the diagnosis of RLS, and to screen for apnea-hypopnea index. Results: Overall, 27% of the cohort was diagnosed with insomnia+RLS. Genotyping results have shown that the three MEIS1 gene variants are only associated to the presence of RLS (all p-value<0.05). The comparison of the allele and the genotype distributions of the CID cohort to the ethnically matched controls and RLS cases confirmed our finding by showing the genotyping distribution similarities between the insomnia-only and the control groups and between the insomnia+RLS and RLS-only groups. Conclusion: Hence, our data does not support the pleiotropic effect of MEIS1 gene, suggesting that this gene is only associated to RLS. It is now clear for future genetic studies the need to isolate CID from other disorders that can cause sleep difficulties, particularly RLS. Support (If Any): NA.